Egfr signaling modulates VM32E gene expression during Drosophila oogenesis - Bernardi, Fabio; Duchi, Serena; Cavaliere, Valeria; Donati, Alessandra; Andrenacci, Davide; Gargiulo, Giuseppe (Development Genes and Evolution, 2007)
Drosophila vitelline membrane gene VM32E is expressed in the follicle cells of the stage 10 egg chamber and shows a peculiar temporal and spatial expression pattern compared to the other members of the same gene family. Previous work has led us to demonstrate that Decapentaplegic (Dpp) signaling represses the expression of the VM32E gene in the centripetal follicle cells. In this paper, we describe another level of complexity of the VM32E gene expression regulation. Through clonal analyses, we show that the expression of the VM32E gene in the main body follicle cells is modulated by the epidermal growth factor receptor (Egfr) activity. In follicle cell clones expressing a constitutively active form of the Egfr, the VM32E gene is downregulated, while the loss of the Egfr activity upregulates VM32E expression. In addition, we show that the ectopic expression of the Egfr-induced ETS transcription factor PointedP2 (PntP2) affects the expression of the VM32E gene. From these results and our previously published data, it appears that the proper patterning of follicle cells, defined by Dpp and Egfr signaling pathways, controls the VM32E gene expression pattern. This may suggest that a fine tuning of the expression of specific eggshell structural genes could be part of the complex process that leads to a proper eggshell assembly.